2004
DOI: 10.1590/s0037-86822004000100002
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions associated with a Fuenzalida-Palacios rabies vaccine: a quasi-experimental study

Abstract: The Fuenzalida-Palacios rabies vaccine has been used in South America for rabies post-exposure prophylaxis. To determine the frequency of adverse reactions associated with this vaccine compared to a control group a quasi-experimental study was carried out in Uberlândia, Brazil, from May 1997 to April 1998. Victims of bites or other injuries by dogs or other mammals and who received or not post-exposure prophylaxis with Fuenzalida-Palacios rabies vaccine were compared as to the occurrence of a list of signs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The side effects of this vaccine included local allergic reactions at the injection site as well as systemic allergies and neurological complications. 3,11 As a result, the Fuenzalida vaccine was discontinued in 2007 and was replaced with a cell culture-derived vaccine. However, people are still concerned about using rabies vaccines, and the fear of side effects remains.…”
Section: Discussionmentioning
confidence: 99%
“…The side effects of this vaccine included local allergic reactions at the injection site as well as systemic allergies and neurological complications. 3,11 As a result, the Fuenzalida vaccine was discontinued in 2007 and was replaced with a cell culture-derived vaccine. However, people are still concerned about using rabies vaccines, and the fear of side effects remains.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of myelin in tissues derived from newborn animals made the SMB vaccine less reactogenic compared to the Semple vaccine. However, research revealed that the vaccine was not free from myelin completely, and the presence of other undesirable components resulted in severe adverse reactions [36]. Hence, in unison with WHO recommendations, the national regulatory authorities across the globe decided to discontinue this vaccine after its decade's long use [37].…”
Section: Myelin-free Tissue Vaccinesmentioning
confidence: 99%
“…The Fuenzalida rabies vaccine was thereby developed using this technique [14]. However, the vaccine was not fully free of brain tissue components such as myelin, and severe adverse reactions were still reported [15]. An alternative approach to overcome these issues employed embryonated eggs, such as chick or duck embryos, as the media to produce rabies vaccines [12].…”
Section: Brief History Of Classical Rabies Vaccinesmentioning
confidence: 99%